Hi I'm having trouble with this question and was hoping for a push in the right direction...

I've been given the boolean function

$\displaystyle f = w \oplus y \oplus xz \oplus wxz \oplus wyz \oplus wxyz$

and been asked to apply the karnaugh map method to it.

However I don't know how to get straight from that function to a Karnaugh map and I'm having trouble with the algebra in trying to get rid of the $\displaystyle \oplus$ signs.

I've gotten as far as

$\displaystyle f = (wy'\vee w'y)(x'\vee z')\vee (w'\vee y)(w\vee y')(xy) \oplus wxz \oplus wyz \oplus wxyz $

and I'm finding the rest of the algebra messy and intimidating. I don't think I'm on the right track.

I'd really appreciate some pointers, thanks in advance!